Utilization of banana [Musa balbisiana cv. Saba (BBB)] midrib as absorbent for copper (II) and Zinc (II). - De la Cruz, Wilyn Joy A. (2013.)
The utilization of banana midrib as an adsorbent for Cu2+ and Zn2+ was studied. Dried and ground banana midrib was treated with hydrogen peroxide (H2O2) and adsorption sites were increased by adding magnesium chloride. The FT-JR spectra of both untreated and pre-treated banana midrib showed that there were different functional groups present which were able to bind with metal ions in the solution. Also, the peak generated at 1710cm-3 on the IR spectrum of the pre-treated adsorbent confirmed the oxidation of the cellulose. Parameters for adsorption such as contact time and adsorbent dose were studied on both untreated and pre-treated adsorbent. The results showed that adsorption for Cu2+ and Zn2+ is higher on untreated adsorbent which is almost twice the adsorption on pre-treated adsorbent. On untreated adsorbent, the adsorption is Zn2+ > Cu2+ while on pretreated adsorbent, the adsorption is Cu2+ > Zn2+. This could be due to the addition of MgCl2 as cation exchanger and Cu2+ has higher affinity to Mg2+ thus lower adsorption for Zn2+., Equilibrium data using pre-treated adsorbnet was described by Langmuir isotherm model for Cu2+ and Zn2+ with correlation coefficient, R2 0.8824 and 0.9066 respectively though <0.95. Untreated adsorbent meanwhile, fit well with Freundlich isotherm model having correlation coefficient, R2 0f 0.9914 for Cu2+ and 0.9678 for Zn2+. The applicability of the adsorbent was tested on Miagao river water and H2O2- treated banana midrib showed higher adsorption efficiency (E) for both metals as compared to untreated adsorbent, 68.72 percent > for Cu2+ and 58.16 percent > 50.10 percent for Zn2+.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Banana